(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the influence of medroxyprogesterone acetate (MGA) supplementation between the 13th and 20th day after Fixed-Time-Artificial Insemination (FTAI), on the conception and gestation rates of Nellore and crossbred cows (Nellore x Angus), pluriparous and lactating. For the study, 349 Nellore cows and 270 crossbred cows were selected, distributed into 1) group G1 (n=176): Nellore cows submitted to the FTAI protocol, without MGA supplementation; 2) group G2 (n=173): Nellore cows submitted to the FTAI protocol, with supplementation for 7 days of MGA® (0.28g/AU/day) from the 13th post-FTAI; 3) group G3 (n=119): crossbred cows: FTAI protocol, without MGA supplementation; 4) group G4 (n=151): crossbred cows: FTAI protocol followed by MGA supplementation for 7 days (0.28g/AU/day), from the 13th to the 20th day after FTAI. For statistical analysis, the procedures MIXED and GLIMMIX from SAS were used. G3 had higher rates of conception (CR=85.7%) and pregnancy (PR=95.8%) at the end of the breeding season (P<0.05), without the interference of supplementation with MGA (P>0.05). G1 females had a lower conception rate (TC=76.7%) (P<0.05), with the use of MGA® (CR-MGA=59.5%), but similar rates of pregnancy (PR=90.3%; PR-MGA=92.5%) to the G2, at the end of the breeding season (P>0.05). When G2 and G4 were compared, we found that crossbred females supplemented had higher rates of conception and pregnancy. In conclusion, crossbred animals have higher conception and pregnancy rates at the end of the breeding season. Besides, we found that Nellore females had a lower conception rate, with the use of MGA® Premix.